Post-election Tunisia: Security issues as a threat to democratisation. Germany should help reform and strengthen the security sector - Christian Mölling; Isabelle Werenfels (Stiftung Wissenschaft und Politik (SWP), 2014)
Tunisia is the only Arab state currently undergoing a democratic transition. But this process is unfolding under increasingly difficult conditions. The economic crisis and the security challenges posed by armed Islamists are exacerbating one another. If Germany does not wish to see a reversal of the political achievements in which it has invested so much, and in order to uphold Tunisia as a beacon for the region, it will have to considerably expand its cooperation on both economic and security issues. Broad and rapid measures aimed at increasing the efficiency and accountability of the security sector could present a positive counterexample to last-ditch arms deliveries to conflict regions. (SWP Comments)
Keywords: 320